Further Evidence That N2pc Reflects Target Enhancement Rather Than Distracter Suppression - Li, Chaojie; Liu, Qiang; Hu, Zhonghua (Frontiers in Psychology, 2018)
The N2-posterior-contralateral (N2pc) component is an index in the domain of event-related potentials for exploring the underlying mechanism of visual-spatial attention. It has been disputed whether the attentional selection reflected by N2pc is primarily due to distracter suppression or target enhancement processes. We addressed this controversy by combining the pop-out item and the target feature, and instructed participants whether the pop-out item included the target feature. Thus, in a visual search task, bilateral visual stimuli including a pop-out item and three distractors were displayed simultaneously. The pop-out detection was analyzed under varying two factors: (a) pop-out item as a target or non-target (b) the distractors containing a target feature or non-target feature. Although all conditions had a salient effect on behavioral performance, the reliable difference of N2pc existed only between the target condition and the non-target condition. These results provided strong support for the hypothesis of target enhancement processes.